(untitled) (Mongolian Journal of Humanities and Social Sciences, 2023)
In this article, based on the documents of the first explanatory dictionary of the Mongolian language, the Twenty-One Dictionary (1717), the characteristics and odd endings of Mongolian verb formation are explained from the point of view of word structure and typology. Verb formation in modern Mongolian can be divided into two categories: forming verbs from free roots and forming verbs from non-free roots. According to the documents of the twenty-first glossary, the variants of “-la” suffix “-lo (u)”, “-lü” suffix, “-na” suffix “-no (u), “-nü” to form verbs from free roots are The unique suffixes are explained by quoting from the dictionary. Also, the suffixes “-ra, -ro, -ri”, “-γa4 + na4”, “-l”, “či-” used to create verbs from non-free roots are analyzed and explained by word structure. Үйл үг бүтээх дагаврын утга, үүргийг тодруулах нь (Хорин нэгт тайлбар толийн жишээн дээр) Хураангуй: Энэхүү өгүүлэлд монгол хэлний ууган тайлбар толь болох Хорин нэгт тайлбар толь бичиг (1717)-ийн баримтад тулгуурлан, монгол хэлний үйл үг бүтээх онцлог, содон дагаврыг үгийн бүтэц, хэв шинжийн үүднээс тайлбарлав. Орчин цагийн монгол хэлний үйл үг бүтээх дагаврыг идэвхтэй язгуураас үйл үг бүтээх, идэвхгүй язгуураас үйл үг бүтээх гэж хоёр ангилна. Хорин нэгт тайлбар толийн баримтаас үзэхэд идэвхтэй язгуураас үйл үг бүтээх “-la” дагаврын хувилбар “-lo (u)”, “-lü” дагавар, “-na” дагаврын хувилбар “-no (u”), “-nü” гэсэн өвөрмөц дагавар буйг толь бичгийн баримтаас эшлэн тайлбарлав. Мөн чөлөөт бус язгуураас үйл үг бүтээх “-ra, -ro, -ri”, “-γa4 + na4”, “-l”, “či-” гэсэн дагаврыг үгийн бүтцээр задлан тайлбарлав. Түлхүүр үг: Үйл үг, үйл үг бүтэх ёс, идэвхтэй язгуур, чөлөөт бус язгуур, дагавар, дагаврын хувилбар